Columbite-Group Minerals from New York Pegmatites: Insights from Isotopic and Geochemical Analyses - Marian V. Lupulescu; Jeffrey R. Chiarenzelli; Mark E. Pecha; Jared W. Singer; Sean P. Regan (Geosciences, 2018)
Columbite crystals from niobium-yttrium-fluorine (NYF) pegmatites lacking zircon or containing metamict cyrtolite were analyzed for major and minor elements (Electron Microprobe (EMP)), trace elements (Laser Ablation-Inductively Coupled Plasma-Mass Spectrometry (LA-ICP-MS)), and U-Pb geochronology (Laser AblationMulti-Collector-Inductively Coupled Plasma-Mass Spectrometry (LA-MC-ICP-MS)). All four pegmatite localities sampled are hosted by the Proterozoic Fordham gneiss and/or Paleozoic Bedford gneiss (Columbite-(Fe); Kinkel and Baylis localities) and the Manhattan Schist of Lower Paleozoic age (Columbite-(Mn); Fort George and Harlem River Drive localities) and yield Neoacadian ages. The weighted average U-Pb ages are 372.2 ± 8.2 Ma (Baylis Quarry), 371.3 ± 7.3 and 383.4 ± 8.9 Ma (Kinkel Quarry); 383 ± 15 Ma (185th St. and Harlem River Drive); and 372 ± 10 Ma (Fort George). A partial metamict zircon (“cyrtolite”) from the Kinkel Quarry yielded a weighted average U-Pb age of 376.9 ± 4.3 Ma. The Neoacadian ages obtained agree with those determined by thermal ionization mass spectrometry (TIMS) for zircon from Lithium-Cesium-Tantalum (LCT) pegmatites from Connecticut and Maine. No pegmatites temporally associated with the Taconic orogeny were found. The size, lack of common Pb, uniform U concentrations across crystal cross-sections, sufficient but moderate uranium concentrations, lack of metamictization, and consistency in U-Pb isotopic ratios for columbite samples BCB-COL, NYSM #25232, and NYSM #525.8 suggests they show promise as potential standards for oxide mineral LA-MC-ICP-MS geochronological analyses, however, additional characterization using ID-TIMS would be necessary to develop as such.